(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Studies on the parasitoid complex of the satin moth Stilpnotia salicis (L.) have been conducted at different locations in Bulgaria during the period 1978-1991. Twenty parasitoid species from the families Braconidae, lchneumonidae, Chalcididae, Torymidae, Scelionidae, Tachinidae and Sarcophagidae were identified. From these, six parasitoid species - three primary [Anastatus bifasciatus (Fonsc.), Exorista mimula (Meig.) and Pseudosarcophaga mamillata Pandelle], and three hyperparasitoids [Theronia atalantae (Poda), Brachymeria minuta (L.) and Brachymeria secundaria (L.)], were new records for the parasitoid complex of this host. The percentage of host egg parasitism caused by Telenomus nitidulus Thoms. varied from 0 to 45.0, with an average of 15.3%. Apanteles melanoscelus (Ratz.) and Meteorus versicolor (Wesm.) parasitized an average of 14.4% of the early-stage larvae of this pest. Most mortality is caused by A. melanoscelus, which, in some cases may parasitize up to 45.5% of the early-stage larvae. Late-stage larvae and pupae of S. salicis are attacked by Pimpla hypochondriaca (Ratz.), T. atalantae (Ichneumonidae), Brachymeria intermedia (Nees) and Pediobius pyrgo Walker (Chalcididae), Monodontomerus aereus Walker (Torymidae), Carcelia exavata (Meig.), Compsilura concinnata (Meig.), Exorista larvarum (L.), E. mimula and Pales pavida (Meig.) (Tachinidae) and P. mamillata (Sarcophagidae). The species of the farnily Tachinidae are most important in reducing the number of the pest. In St. salicis populations in Bulgaria the avarage mortality caused by parasitoid insects was 47.3%, and in some sites it reached 89.1%. Parasitoids play an important role in the regulation of satin moth populations and for the stability of poplar stands.